ISLAMIC FINANCIAL DEVELOPMENT AND ECONOMIC GROWTH IN NIGERIA: A BOUNDS TESTING APPROACH - Tasiu Tijjani Sabiu; Muhamad Abduh (Journal of Islamic Monetary Economics and Finance, 2020)
Using a bounds testing approach to the cointegration and error correction method developed within the autoregressive distributed lag (ARDL) framework, this paper analyses the short- and long-run dynamic relationships between Islamic financial development and economic growth in Nigeria. Quarterly time-series data (2012:1 to 2019:3) are employed for the variables, together with non-interest bank financing to the private sector and real gross domestic product as indicators of Islamic financial development and economic growth respectively. The results indicate a significant short- and long-run relationship between Islamic financial development and economic growth. The relationship, however, is neither Schumpeter’s supply-leading nor Robinson’s demand-following type; rather, it appears to be bi-directional. In addition, empirical evidence is found that underscores the important role of Islamic bank financing in the economic performance of Nigeria. The paper recommends that improvement of the Islamic financial system in Nigeria may foster economic development and enhance welfare and poverty alleviation in the long run.